Технология кейс-стади как эффективное средство формирования образовательной самостоятельности будущих педагогов - Лебедева, К.С. (My University, 2016)
The article considers the problem of application of technology a case-stadi as an effective remedy of formation of educational independence of future teachers. The author shows the content of the concept of "case studies", describes technology components, as well as the results of testing of the case at the university. On the basis of theoretical material and the data obtained during experimental work the main stages of realization of technology are allocated.
Keywords: technology; case studies; innovation; educational autonomy; teacher